Determination of Critical Node in The Java Sumatra Kalimantan Submarine Cable Communication System - Rachmadini, Haliza Suci; Aman, Amril; Paruhum Silalahi, Bib (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2023)
Disruption of the Java Sumatra Kalimantan (Jasuka) submarine cable communication system significantly impacted the smooth flow of communications. To reduce the impact, the detection of critical nodes in the network uses the critical node detection method to identify the most important nodes in the Jasuka network. This study aims to apply the critical node detection method as integer linear programming on the Jasuka network to obtain critical nodes by minimizing the number of paired connections on the nodes. The data in this research comes from the Jasuka network, represented as nodes and edges, and then analyzed using Python 3.11 software. The results showed that the critical node of the Jasuka submarine cable communication system is located at index 5 and 14 or the landing point Dumai, Riau and Palembang Jambi. The critical node on the Jasuka network can be a reference for Telkom Indonesia to pay special attention to the landing point because the damage will impact the entire network.